The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.6007/ijarbss/v8-i2/3967
|View full text |Cite
|
Sign up to set email alerts
|

Destination Image through the Perspectives of Travellers to State of Perak, Malaysia

Abstract: In selecting tourism destination, travelers based their decisions on the perception of destination image attributes which they received from multiple information sources. Thus, the objective of this study was to explore and identify the dimension of image as perceived by travelers to the state of Perak, Malaysia by employing an exploratory factor analysis. The results exhibited that local attraction and facilities is the main indicator that attracts tourists to Perak followed by natural setting. The findings a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Destination images consist of mainly cognitive and affective perspectives, whereby cognitive components include the structural and physical elements of the destination whereas affective components are made up of relaxing atmosphere, pleasant and safe surroundings (Baloglu & McCleary, 1999). In comparison to local attraction sites and infrastructure, destination image was the strongest predictor of visit intention (Jamaludin, Mokhtar, & Aziz, 2018). Past studies confirmed stated that a positive destinations image contributes to the tourists' visit intention and played an important role in tourists' decision making (Chen & Tsai, 2007;Siti-Nabiha et al, 2008).…”
Section: Destination Imagementioning
confidence: 99%
“…Destination images consist of mainly cognitive and affective perspectives, whereby cognitive components include the structural and physical elements of the destination whereas affective components are made up of relaxing atmosphere, pleasant and safe surroundings (Baloglu & McCleary, 1999). In comparison to local attraction sites and infrastructure, destination image was the strongest predictor of visit intention (Jamaludin, Mokhtar, & Aziz, 2018). Past studies confirmed stated that a positive destinations image contributes to the tourists' visit intention and played an important role in tourists' decision making (Chen & Tsai, 2007;Siti-Nabiha et al, 2008).…”
Section: Destination Imagementioning
confidence: 99%
“…The ideas of extrinsic motivations, emotion and cognitive image were introduced and developed as an extension of the S-O-R paradigm based on theories of environmental psychology. The Mehrabian-Russell modified version of the S-O-R environmental psychology model was used for the current investigation as it has been extensively used in earlier studies to investigate how the environment influences behaviour by affecting emotion and cognitive image (Jeong et al, 2020;Mun et al, 2018). International education tourists are critical to the global travel industry as they travel frequently to learn about different cultures and local languages.…”
Section: Discussionmentioning
confidence: 99%
“…All construct items were adopted from other studies and modified to fit the current study. For the demographic data, the items were adopted from (Mun et al, 2018). The measurement items for extrinsic motivation were adopted from Ojo et al (2016) and Negm (2018).…”
Section: Research Methodology Instrument Developmentmentioning
confidence: 99%
“…This study focuses on the Geographical landscape as an initial mapping of the cultural landscape as it has a physical character that is identical to easily be navigated by the GIS technology. Mapping these typologies of Perak's cultural landscape helps to identify and understand the distribution, diversity, and interconnectedness of cultural elements within the region [8]. It supports cultural preservation, tourism development, community engagement, and sustainable management of the cultural heritage of Perak.…”
Section: Cultural Landscape Of Perakmentioning
confidence: 99%